Sagot :
Step-by-step explanation:
[tex]x {}^{2} - 5x = 2[/tex]
[tex]x {}^{2} - 5x - 2 = 0[/tex]
[tex]x = \frac{ - ( - 5) \frac{ + }{} \sqrt{( - 5) {}^{2} - 4 \times 1 \times ( - 2) } }{2 \times 1} [/tex]
[tex]x = \frac{5 \frac{ + }{} \sqrt{25 + 8} }{2} [/tex]
[tex]x = \frac{5 \frac{ + }{} \sqrt{33} }{2} [/tex]
[tex]x = \frac{5 + {} \sqrt{33} }{2} \\ x = \frac{5 - \sqrt{33} }{2} [/tex]
[tex]x1 = \frac{5 - \sqrt{33} }{2} \\ x2 = \frac{5 + \sqrt{33} }{2} [/tex]
Alternate form:
x1 ≈ -0.372281
x2 ≈ 5.37228